A federal survey deficiency citation is needed for resident-to-resident aggression in U.S. nursing homes. Issue 4 (8th August 2017) - Caspi, Eilon
ABSTRACT: Resident-to-resident aggression (RRA) in nursing homes is a prevalent and concerning public health problem. A rapid growth in the number of research studies has led to advancements in understanding and awareness of these incidents. However, no state survey deficiency citation (F-Tag) currently exists to capture RRA in a structured way in the Centers for Medicare & Medicaid Services' (CMS) nursing homes F-Tags Coding System. This omission represents a major barrier to State Survey Agencies, CMS, consumers, and care advocacy organizations' efforts to keep vulnerable and frail residents safe and free from psychological harm. The commentary makes the case for development and implementation of a new RRA-specific F-Tag by identifying 20 problem areas and the ways in which this F-Tag could address them. The new F-Tags Coding System (part of the new Federal Nursing Home regulations) represents a rare and time-sensitive opportunity to bridge this major gap in practice, research, and policy.